TRANSPATH ®—A High Quality Database Focused on Signal Transduction. Issue 2 (2004) - Choi, Claudia; Krull, Mathias; Kel, Alexander; Kel-Margoulis, Olga; Pistor, Susanne; Potapov, Anatolij; Voss, Nico; Wingender, Edgar
Abstract : TRANSPATH ® can either be used as an encyclopedia, for both specific and general information on signal transduction, or can serve as a network analyser. Therefore, three modules have been created: the first one is the data, which have been manually extracted, mostly from the primary literature; the second is PathwayBuilder ™, which provides several different types of network visualization and hence faciliates understanding; the third is ArrayAnalyzer ™, which is particularly suited to gene expression array interpretation, and is able to identify key molecules within signalling networks (potential drug targets). These key molecules could be responsible for the coordinated regulation of downstream events. Manual data extraction focuses on direct reactions between signalling molecules and the experimental evidence for them, including species of genes/proteins used in individual experiments, experimental systems, materials and methods. This combination of materials and methods is used in TRANSPATH ® to assign a quality value to each experimentally proven reaction, which reflects the probability that this reaction would happen under physiological conditions. Another important feature in TRANSPATH ® is the inclusion of transcription factor–gene relations, which are transferred from TRANSFAC ®, a database focused on transcription regulation and transcription factors. Since interactions between molecules are mainly direct, this allows a complete and stepwise pathway reconstruction from ligands to regulated genes. More information is available at www.biobase.de/pages/products/databases.html.